Exposure to benzotriazoles and benzothiazoles in Czech male population and its associations with biomarkers of liver function, serum lipids and oxidative stress - Pálešová, Nina; Bláhová, Lucie; Janoš, Tomáš; Řiháčková, Katarína; Pindur, Aleš; Šebejová, Ludmila; Čupr, Pavel (International archives of occupational and environmental health, 2024)
INTRODUCTION: Benzotriazoles and benzothiazoles (BTs) are high-production volume chemicals as well as widely distributed emerging pollutants with potential health risk. However, information about human exposure to BTs and associated health outcomes is limited. OBJECTIVE: We aimed to characterise exposure to BTs among Czech men, including possible occupational exposure among firefighters, its predictors, and its associations with liver function, serum lipids and oxidative stress. METHODS: 165 participants (including 110 firefighters) provided urine and blood samples that were used to quantify the urinary levels of 8 BTs (high-performance liquid chromatography-tandem mass spectrometry), and 4 liver enzymes, cholesterol, low-density lipoprotein, and 8-hydroxy-2'-deoxyguanosine. Linear regression was used to assess associations with population characteristics and biomarkers of liver function, serum lipids and oxidative stress. Regression models were adjusted for potential confounding variables and false discovery rate procedure was applied to account for multiplicity. RESULTS: The BTs ranged from undetected up to 46.8 ng/mL. 2-hydroxy-benzothiazole was the most predominant compound (detection frequency 83%; median 1.95 ng/mL). 1-methyl-benzotriazole (1M-BTR) was measured in human samples for the first time, with a detection frequency 77% and median 1.75 ng/mL. Professional firefighters had lower urinary 1M-BTR compared to non-firefighters. Urinary 1M-BTR was associated with levels of γ-glutamyl transferase (β = - 17.54%; 95% CI: - 26.127, - 7.962). CONCLUSION: This is the first study to investigate BT exposure in Central Europe, including potentially exposed firefighters. The findings showed a high prevalence of BTs in the study population, the relevance of 1M-BTR as a new biomarker of exposure, and an urgent need for further research into associated adverse health outcomes.
Keywords: oxidační stres; Triazoles; 8-Hydroxy-2'-Deoxyguanosine; Male; biologické markery; Human biomonitoring; Oxidative stress; Occupational Exposure; triazoly; Biomarkers; Serum lipids; Česká republika; Cholesterol; pracovní expozice; Adult; dospělí; mužské pohlaví; hasiči; Firefighters; benzothiazoly; Czech Republic; deoxyguanosin; cholesterol; lipidy; Benzothiazoles; Liver function; lidé; játra; Humans; Benzothiazole; Benzotriazole; Lipids; Liver; Oxidative Stress; 8-hydroxy-2'-deoxyguanosin; lidé středního věku; Deoxyguanosine; Middle Aged